Sunflower nutrition irrigated with domestic sewage treated - Dantas, Daniel Costa; Silva, Ênio Farias de França e; Dantas, Mara Suyane Marques; Silva, Gerônimo Ferreira da; Rolim, Mario Monteiro (Comunicata Scientiae, 2019)
This study aimed to evaluate the nutritional status of the sunflower (Helianthus annus L.) irrigated with domestic effluents. The study was performed in a pilot sewage treatment plant, where the treatments were composed by the combination of two factors: types of water (A1 - effluent treated by UASB reactor; A2 – effluent treated with digester decant and anaerobic filtering; A3 – effluent treated with anaerobic filtering; and A4 – water supply) and irrigation depths (L1 - equal to the crop evapotranspiration (ETc) and L2 – 1.2 ETc. The experimental design was in randomized blocks, in a 4 x 2 factorial scheme, with four replications. At 96 days after sowing, the leaves, capitulum, and achenes were collected for the concentration evaluation of N, P, K, Ca, Mg and S. The analyses of variance were performed based on the concentration of the nutrients in the respective organs; when significant, they were analyzed by orthogonal contrasts. The sunflower nutritional status was influenced by the types of treatment for the domestic sewage, especially regarding N, Ca and S, and by the irrigation depths; the sunflower crop presented a better nutritional balance when irrigated with treated domestic effluents; with the application of the water supply only, the nutritional supply of the P and S, is necessary.